Sequence analysis and in vitro expression of genes 6 and 11 of an ovine group B rotavirus isolate, KB63: Evidence for a non-defective, C-terminally truncated NSP1 and a phosphorylated NSP5 - Shen, S. (2014)
Journal of General Virology